The perception and brand attitude of paid versus organic social media advertising: Case study of the Mamee Company - Nizam, Nurul Zarirah; Kamarudin, Nurhayati; Bakri, Mohammed Hariri (Human Resource Management Academic Research Society (HRMARS), 2024)
In the context of one of the marketing mix elements (promotion), social media advertising is vital for enhancing consumer awareness and perception of a company's products and services. In employing the Theory of Advertising Value framework, this research aims to establish a model to comprehend the effectiveness of paid versus organic social media advertising based on the perception and brand attitude of Generation Z. The location study will be conducted in Melaka because there are more urban areas such as that have higher social media usage due to greater access to internet connectivity, digital devices, and younger demographic that tends to be more engaged with social media platforms. Overall, 175 social media users among Gen Z in Melaka state were chosen using convenience sampling. Generation Z was chosen because they grow in a technological world and are interconnected with social media platforms. This quantified research accumulated survey questionnaire data to evaluate the hypotheses and the relationship between independent and dependent variables. This study revealed that all four advertising values enormously affect Generation Z's perception and brand attitudes: informativeness, entertainment, irritation, and credibility. The researcher leveraged SPSS version 29.0 to perform an explanatory analysis, Pearson correlation analysis, multiple regression analysis, and validity and reliability analysis on the information collected intended for the present research. In practical contribution, the expected outcome contributes to the expanded collection of information regarding the factors that inspire food and beverage (F&B) companies to choose suitable mediums for product promotion, whether paid or organic social media advertising and thus alter their strategy for social media advertising.